2002
DOI: 10.1016/s0925-4773(01)00562-7
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin expression in early development is associated with vasculogenesis and angiogenesis

Abstract: Endoglin is an auxiliary receptor for the transforming growth factor-beta family of cytokines and is required for angiogenesis and heart development. Endoglin expression during mouse embryogenesis was analysed by monitoring beta-galactosidase expression from a lacZ reporter cassette inserted downstream of the endoglin promoter. Expression was first detected at 6.5 days post-coitum (dpc) in the amniotic fold and developing allantois. Between 7.5 and 8.5 dpc, endoglin was expressed in endothelial cells of the yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 13 publications
5
66
0
2
Order By: Relevance
“…The occurrence of arteriovenous malformations in HHT patients and high endoglin expression in normal developing heart valves pointed to other roles for endoglin in cardiovascular development [1]. This was confirmed in the endoglin knockout mouse, in which we, and others, showed that lack of endoglin expression causes failure of angiogenesis, best seen in the yolk sac, as well as defects in endocardial cushion formation [2][3][4].…”
Section: Referencesmentioning
confidence: 53%
See 1 more Smart Citation
“…The occurrence of arteriovenous malformations in HHT patients and high endoglin expression in normal developing heart valves pointed to other roles for endoglin in cardiovascular development [1]. This was confirmed in the endoglin knockout mouse, in which we, and others, showed that lack of endoglin expression causes failure of angiogenesis, best seen in the yolk sac, as well as defects in endocardial cushion formation [2][3][4].…”
Section: Referencesmentioning
confidence: 53%
“…We have shown Igf-2 inhibits MD skeletal muscle apoptosis and stabilizes dystrophic phenotype [1,2]. Igf-2 may thus be suitable for therapeutic use in MD, delivered directly to skeletal muscles.…”
Section: Trophoblast Stem Cells: An In Vitro Model For Imprinted X Inmentioning
confidence: 91%
“…30,35 In the sinusoidal EC of the liver, Eng expression was strong, whereas Alk1 expression was undetectable. 11,38 In addition, the arterial-EC-predominant expression of Eng was not as apparent as that of Alk1. 38 The data presented in this paper provide useful information for utilizing Alk1-lacZ reporter lines and Alk1-null embryos in the investigation of placental vascular development as well as of pathogenetic mechanisms for HHT and preeclampsia.…”
Section: Alk1 In Placental Vascular Developmentmentioning
confidence: 98%
“…During development, ENG and ALK1 present very similar expression patterns in areas of vasculogenesis (yolk sac, early embryonic vasculature) and angiogenesis (throughout the late embryonic vascular endothelium) (Jonker and Arthur, 2002;Roelen et al, 1997;Seki et al, 2003). ENG is detected in veins, liver sinusoidal endothelial cells and arteries, while ALK1 is only detected in developing arteries, suggesting a role in arterial differentiation (Jonker and Arthur, 2002;Seki et al, 2003).…”
Section: Normal and Tumor Endothelial Expression Of Eng And Alk1mentioning
confidence: 99%